Effect of pre-strain on oxidation behaviour of nickel-based superalloys in air at 700 °C. (15th May 2022) - Lee, Cheol Min; Han, Young-Soo; Jeong, Jae Suk; Jung, Woo Sang; Song, Seok Hyun; Kim, Ju-Seong
Abstract: The effect of pre-strain on oxidation behaviour of nickel-based superalloys was analysed using alloys 263 and 740H. Both alloys were subjected to tensile tests followed by oxidation tests at 700 °C in air. At higher pre-strain, both alloys exhibited higher oxidation rates and more oxide spallation. Microstructures were examined using various techniques (XRD, SEM, EBSD, and TEM). It was found that the pre-strain accelerated the formation of internal oxides. The defects that formed during the tensile tests apparently acted as oxygen diffusion channels from the oxide/metal interface to the inside of the metal substrate. Graphical Abstract: ga1 Highlights: Effect of pre-strain on oxidation behaviour of Ni-based superalloys was analysed. The oxidation resistance decreased with increasing pre-strain. The microstructures were examined in detail using XRD, SEM, EBSD, and TEM.